Analisis Faktor Capaian Realisasi Penerimaan Retribusi Jasa Angkutan Sungai dan Penyeberangan pada Dinas Perhubungan Kota Palembang - Darma Yanti; Rosalina Ghozali (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2020)
River and crossing service levies are transport activities using ships carried out in the river, and crossings to transport passengers, goods and or animals organized by river and crossing companies. The factor of not achieving the realization of the revenue of river transportation and crossing retribution services in the Palembang City Transportation Agency, setting unrealistic targets is constrained by a lack of legal basis so as to achieve the desired target cannot be achieved and limited authority for officers who withdraw fees due to regulatory regulations Number 35 of 2017 concerning escorts that are still in conflict with the Laws Regulations, Ministerial Regulations, Government Regulations, and Regional Regulations. The collection of retribution is also experiencing leakage or breakthrough due to the effectiveness of the imposition of sanctions and the lack of facilities and infrastructure in the field. The service is not yet prime due to limited human resources or field implementation officers. The levies collection officer is not unwilling to provide services and human resources, but also because of conflicting rules that prevent officers from carrying out a complete withdrawal. Officers move with the rules set by the City Government so that their authority is limited.